Neutralizing Antibodies Induced by Gene-Based Hydrodynamic Injection Have a Therapeutic Effect in Lethal Influenza Infection - Yamazaki, Tatsuya; Nagashima, Maria; Ninomiya, Daisuke; Ainai, Akira; Fujimoto, Akira; Ichimonji, Isao; Takagi, Hidekazu; Morita, Naoko; Murotani, Kenta; Hasegawa, Hideki; Chiba, Joe; Akashi-Takamura, Sachiko (Frontiers in Immunology, 2018)
The influenza virus causes annual epidemics and occasional pandemics and is thus a major public health problem. Development of vaccines and antiviral drugs is essential for controlling influenza virus infection. We previously demonstrated the use of vectored immune-prophylaxis against influenza virus infection. We generated a plasmid encoding neutralizing IgG monoclonal antibodies (mAbs) against A/PR/8/34 Influenza virus (IAV) hemagglutinin (HA). We then performed electroporation of the plasmid encoding neutralizing mAbs (EP) in mice muscles and succeeded in inducing the expression of neutralizing antibodies in mouse serum. This therapy has a prophylactic effect against lethal IAV infection in mice. In this study, we established a new method of passive immunotherapy after IAV infection. We performed hydrodynamic injection of the plasmid encoding neutralizing mAbs (HD) involving rapid injection of a large volume of plasmid-DNA solution into mice via the tail vein. HD could induce neutralizing antibodies in the serum and in several mucosal tissues more rapidly than in EP. We also showed that a single HD completely protected the mice even after infection with a lethal dose of IAV. We also established other isotypes of anti-HA antibody (IgA, IgM, IgD, and IgE) and showed that like anti-HA IgG, anti-HA IgA was also effective at combating upper respiratory tract IAV infection. Passive immunotherapy with HD could thus provide a new therapeutic strategy targeting influenza virus infection.